The Role of Corporate Social Responsibility (CSR), Financial Literacy, and Time Value of Money (TVM) in Digital Investment Decision Making: A Literature Review - Ari Indra Wahyu; Muchriana Muchran (Pustaka Digital Indonesia, 2026)
The urgency of this study arises from the rapid growth of digital investment platforms in Indonesia amid relatively low financial literacy. Integrating financial literacy, TVM, and CSR is essential to understand investor behavior, mitigate irrational decision making, and support sustainable, value-based digital investment practices in emerging markets. This study explores the role of Corporate Social Responsibility (CSR), financial literacy, and the Time Value of Money (TVM) in shaping digital investment decision-making among Indonesia’s younger generation. Amidst the rise of digital finance platforms and increased youth participation in investment, this narrative literature review synthesizes findings from 24 selected studies published between 2020 and 2024. The review reveals that low financial literacy remains a barrier to informed investment, leading to impulsive and trend-driven behavior. Understanding TVM, as a foundational concept in finance, significantly enhances long-term investment planning and risk assessment. Moreover, CSR has emerged as a key non-financial factor influencing investment preferences, particularly among Gen Z and millennials who prioritize value-based and socially responsible investing. The findings underscore the necessity of integrating financial literacy and CSR considerations into digital investment strategies. The study also identifies the potential of gamified and tech-based financial education to increase engagement and comprehension among young investors. This review offers valuable insights for policymakers, educators, and fintech platforms to promote inclusive, ethical, and informed investment behavior in Indonesia’s evolving digital economy.